The Application of Metabolomic Profiling to the Effects of Physical Activity - Daskalaki, Evangelia; Easton, Chris; G. Watson, David (Current Metabolomics, 2014)
Physical activity and exercise are potent lifestyle interventions for the reduction of several psycho- somatic risks, including cardiovascular disease, diabetes and mild-to-moderate depression. The current review describes the studies which have utilised a metabolomics/ metabolite profiling approach in combination with exercise in the period between 1999-2014 in predominantly healthy subjects (N:64) and in a smaller subset of patient cohorts (N:10) between 2011-2014. A broad range of intervention types were used in both healthy and patient cohorts with varying exercise regimes with or without supplement use. Effects on purine metabolism, which have been known for over 40 years, were by far the most well-cited and persistent finding. Other reported effects included observations of: glucocorticoid and androgen metabolism, glycolysis and Krebs cycle, gluconeogenesis, fatty acid metabolism, fatty acid oxidation and pantothenic acid, amino acid oxidation, tryptophan metabolism and effects on microbiome metabolites. The discussion section draws observations from the very disparate studies together and links them to the general aspects of human metabolism.
Keywords: Human